2011
DOI: 10.1093/jxb/err395
|View full text |Cite
|
Sign up to set email alerts
|

pH regulation in anoxic rice coleoptiles at pH 3.5: biochemical pHstats and net H+ influx in the absence and presence of NO3−

Abstract: During anoxia, cytoplasmic pH regulation is crucial. Mechanisms of pH regulation were studied in the coleoptile of rice exposed to anoxia and pH 3.5, resulting in H+ influx. Germinating rice seedlings survived a combination of anoxia and exposure to pH 3.5 for at least 4 d, although development was retarded and net K+ efflux was continuous. Further experiments used excised coleoptile tips (7–10 mm) in anoxia at pH 6.5 or 3.5, either without or with 0.2 mM NO3−, which distinguished two processes involved in pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 47 publications
0
30
1
Order By: Relevance
“…5C). Furthermore, excised coleoptiles at 0Á3 mM NaCl also accumulated Cl À at 0Á5 lmol g À1 f. wt h À1 between 60 and 84 h of anoxia (Greenway et al, 2012), although this did not occur in the present experiments (Fig. 6B).…”
Section: Low Coupling Ratio Of Hcontrasting
confidence: 62%
See 3 more Smart Citations
“…5C). Furthermore, excised coleoptiles at 0Á3 mM NaCl also accumulated Cl À at 0Á5 lmol g À1 f. wt h À1 between 60 and 84 h of anoxia (Greenway et al, 2012), although this did not occur in the present experiments (Fig. 6B).…”
Section: Low Coupling Ratio Of Hcontrasting
confidence: 62%
“…Importantly, in the coleoptile of anoxic rice seedlings, Na þ and Cl À as high as 140 mM can function as 'cheap' osmolytes. Consistently, anoxic rice coleoptiles can transport Cl À against its free energy gradient (Zhang and Greenway, 1995;Greenway et al, 2012).…”
Section: Fig 2 Kmentioning
confidence: 87%
See 2 more Smart Citations
“…Reggiani et al (1993, 1995) suggested that nitrate is assimilated in rice seeds germinating under anaerobic conditions. This hypothesis was supported by the studies of Fan et al (1997) in rice coleoptiles and recently, Greenway et al (2012) reported that nitrate is converted to ammonium in anoxic rice coleoptiles, which would maintain the pHstat. However, nitrate is quickly reduced in anaerobic soils and its implication in the internal pH balance of rice under anoxic stress is not clear (Greenway et al, 2012).…”
Section: Other Traits Associated With Anaerobic Germinationmentioning
confidence: 58%